Effect of Corn Extract and Solution of PEG to Increase Viability and Vigour of Sweet Corn Seed Deterioration at Different Incubation Periods - Herma Julendri; . Halimursyadah; . Hasanuddin (Syiah Kuala University, 2015)
This study aims to determine the combination of young corn extract and PEG with an incubation period of seed viability and vigor of the sweet corn expired. The study carried out at the Laboratory of Seed Science and Technology Faculty of Agriculture, Syiah Kuala University, Darussalam-Banda Aceh, which lasted from December 2012 to July 2013. Materials used in this study is Expired sweet corn seed with 50% germination. Other materials used are corn extract, PEG 6000, and distilled water. This research used Completely Randomized Design (CRD) factorial 4 x 3, so there are 12 combinations of treatments. Each repeated three times, in order to obtain 36 units of the experiment. Young corn extract concentration factor and solution PEG-2 bar consists of 4 levels, namely: control, 5% + - 2Ψ , 10% + - 2Ψ, and 15% + - 2Ψ. Factors incubation period consists of 3 levels : 18 hours, 24 hours, and 30 hours. Variables measured were potential growth, germination, speed of growth, growing unanimity, vigor index and normal seedling dry weight. The results showed that the concentration of young corn extract very significant effect on the potential variables grow, germination, growing simultaneity, speed of growth, vigor index and normal seedling dry weight. The incubation period of very significant effect on germination variables, simultaneity growth, speed of growth and vigor index. The incubation period significantly affect the potential growth and seedling dry weight normal. There is a significant interaction between young corn extract concentration and incubation period of the vigor index variables. Control treatment (water) with an incubation period of 18 hours is recommended as an alternative to improve the viability and seed vigor of sweet corn expired.